Oral-clinical findings and management of epidermolysis bullosa - (:unkn) unknown (Journal of Clinical Pediatric Dentistry, 2005)
Epidermolysis bullosa (EB) is a diverse group of disorders that have as a common feature blister formation with tissue occuring at variable depths in the skin and/or mucosa. This article reports two cases of EB and review oral- clinical findings of the EB types and approaches for managing the oral- clinical manifestations. While systemic treatment remains primarily palliative, it is possible to prevent destruction and subsequent loss of the dentition through appropriate interventions and dental therapy.